2015
DOI: 10.1002/ejp.669
|View full text |Cite
|
Sign up to set email alerts
|

Patients with complex regional pain syndrome overestimate applied force in observed hand actions

Abstract: We propose that the overestimation of force is explained both by the pain elicited by the observation and by the abnormal sensorimotor integration that is associated with perception of increased effort. This visually elicited unpleasantness and painfulness may promote avoidance of viewing own actions, further impairing the patients' motor performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Sensorimotor conflicts can also occur in other chronic pain conditions associated with altered body perception. Individuals with complex regional pain syndrome (CRPS) report pain disproportionate to the original injury, perceive alterations in the size and shape of their painful limb (Moseley, 2008;Peltz, Seifert, Lanz, Müller, & Maihöfner, 2011) and overestimate the force exerted in observed hand actions (Hotta et al, 2015). Individuals with fibromyalgia (FM) and arthritis report sensations of excessive swelling (McCabe et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Sensorimotor conflicts can also occur in other chronic pain conditions associated with altered body perception. Individuals with complex regional pain syndrome (CRPS) report pain disproportionate to the original injury, perceive alterations in the size and shape of their painful limb (Moseley, 2008;Peltz, Seifert, Lanz, Müller, & Maihöfner, 2011) and overestimate the force exerted in observed hand actions (Hotta et al, 2015). Individuals with fibromyalgia (FM) and arthritis report sensations of excessive swelling (McCabe et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…A substantial number of CRPS patients report "neglect-like" symptoms (Frettlöh, Hüppe, & Maier, 2006;Galer & Jensen, 1999;Galer et al, 1995) and more complex instances of "body perception disturbance" (Lewis, Kersten, McCabe, McPherson, & Blake, 2007). Experimental studies have shown that CRPS patients tend to perceive their affected hand as larger than it actually is (Moseley, 2005), exhibit shifts in the perceived visual body midline (Reinersmann et al, 2011;Sumitani et al, 2007), cannot accurately determine their affected limb's position in space (Lewis et al, 2010) and misjudge applied force when watching a hand grasp an object (Hotta et al, 2015). These findings point to a variety of potentially involved neurophysiological processes.…”
Section: Integration With Previous Findings and Outlookmentioning
confidence: 99%
“…During fMRI scanning, the subjects viewed the same 3.2-second video clips of hand actions that we applied in our previous study in which the stimuli appeared unpleasant and even painful for the patients to observe. 31 In the current experiment, the video clips were shown in 4-clip blocks (Fig 2). Each of the 48 blocks contained videos of hand actions in 1 of 3 possible categories: either left or right hand remaining static (STATIC condition), repeating gentle movements of opening and closing the fist (FIST), or squeezing an object with maximum force (SQUEEZE; the squeezed objects are presented in Supplementary Fig 1).…”
Section: Experimental Designmentioning
confidence: 99%
“…To familiarize the subjects with the hand actions, before scanning we asked them to perform the actions and then view the video stimuli (for the protocol details, see Hotta et al 31 ). The stimuli were shown in conditionwise blocks, and after each block, the subjects rated their level of pain and valence during the observation on the 11-point numeric rating scale (pain: 0 = no pain, 10 = extreme pain; valence: 0 = very pleasant, 5 = neutral, 10 = very unpleasant).…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation